Staphylococcal Toxic Shock Syndrome Complicating Influenza A Infection in a Young Child. (26th May 2011) - Peters, Timothy R.; Hammon, Dudley E.; Jarrah, Rima J.; Palavecino, Elizabeth L.; Blakeney, Elizabeth S.; Poehling, Katherine A.
Abstract : Toxic shock syndrome (TSS) is a potentially lethal but rare complication of influenza infection. We report a case of TSS and influenza A infection in a 5-year-old boy without respiratory symptoms, in whom tracheal aspirate bacterial culture grew a toxin-producing strain of Staphylococcus aureus . Bacterial culture of the upper respiratory tract should be considered in patients with influenza-associated toxic shock syndrome.